Passive forward scatter radar based on LTE signal for vehicle detection and classification - Abdul Aziz, Noor Hafizah (2018)
Passive bistatic radar (PBR) system can utilise suitable signal from illuminator of opportunity to improve radar proficiency. In conventional PBR, a heterodyne receiver and concept is employed. This is due to the PBR requiring reference signal from a direct transmission for synchronization, and then the signal is down converted to the base band where target detection is evaluated by analyzing the ambiguity function of the received signal. On the other hand, by using the forward scattering phenomena and technique in specific mode of PBR, the operation can be further enhanced and improved especially in target detection and classification. This specific system is identified as the passive forward scattering radar (FSR). One of the main condition of passive FSR is the operational mode limited to within the radar baseline. In this scenario, the desired received signal is formed through the shadowing of a direct signal by the target shape rather than back scattering signal from the target such as in conventional radar system. Passive forward scattering radar system offers a number of advantages including enhanced target cross section, long coherent intervals of the receiving signal, absence of signal fluctuations, reasonably simple hardware, economical as it does not need a transmitter system and a spectrum allocation, practically unseen to surveillance receivers, portable due to its smaller size, no synchronization needed for reference signal from direct signal of illuminator, straightforward signal pre-processing for target detection and enhanced classification capability. Thus, the aim of this thesis is to develop and prove the concept of passive forward scattering radar especially for ground detection and classification. The objective is to implement the experimental analysis and results for vehicle detection and classification by exploiting the latest 4G LTE technology signal. This thesis clarifies in details the LTE based passive forward scatter radar receiver circuit, the detection scheme and the classification algorithm. In addition, the proposed passive forward scatter radar circuit employed the self-mixing technique at the receiver, hence it did not require a synchronization signal from the LTE base station. The classification capability in passive forward scattering radar increases the effectiveness of the system. Three vehicle categories with different sizes and shapes were tested, namely Compact, Saloon and Small Sport Utility Vehicle (SUV). The passive FSR experiment results show that the vehicles were successfully detected, even by raw received signals without any complicated signal processing techniques and the proposed classification system provided outcomes of satisfactory classification performance. The Doppler spectrum scattered by the vehicle is used as the features for input to the classification system. The classification algorithm was developed based on Principal Component Analysis (PCA) and k-Nearest Neighbours (k-NN). In addition, the baseline crossing range distance from the radar receiver, as well as vehicle’s speed, was successfully predicted. In general this thesis presents the first classification analysis and performance for the passive forward scatter radar system. The great potential of the passive forward scatter radar system provides a new research area in passive radar that can be used for diverse applications. The thesis also proved that if the FSR mode can be integrated or hybrid with the conventional passive radar system and still have similar performance competency, the system can achieve tremendous improvement. Hence, it opens up a new frontier in passive radar that can be used for many applications including border protection, microwave fences, building monitoring, traffic surveillance, and so forth.